Scientific Publication Article Development Training for SMK Teachers - Rida Prihatni; Ati Sumiati; Tuty Sari Wulan; Siti Nurjanah (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
The purpose of implementing this community service is to provide information, knowledge, and equip teachers in arrange article ready scientific for published in journal scientific, grow atmosphere academic environment school so that could repair quality education and learning with to do activity study. The methods used in this activity include: (a) lectures or material delivery or information presentation for materials related to making scientific articles for publication, (b) questions and answers that provide opportunities for teachers to explore as much knowledge as possible about writing scientific articles, and (c) simulations to provide opportunities to practice the acquired training materials. The results of the implementation of community service can be felt by the community service team and participants. The training that has been carried out has gone well, smoothly in accordance with the goals to be achieved in this activity, and is very satisfying. The YPPD Vocational School teachers gain knowledge and experience sharing about techniques for writing scientific articles and publications to journals and also expect there will be assistance from FE UNJ lecturers in making articles so that they can be published in scientific journals. This is a good response from the training participants with training in the preparation of scientific article publications for SMK teachers.